2010
DOI: 10.2135/cropsci2009.11.0641
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence in Maize: Isolation Distance in Dependence on Conventional Maize Field Depth and Separate Edge Harvest

Abstract: The most reliable and practicable measure in assuring coexistence in respect to pollen‐mediated gene flow from genetically modified (GM) to conventional maize (Zea mays L.) is an isolation distance separating GM and non‐GM fields. Therefore, we tested distances between 24 and 102 m at three sites in northern Germany using a field orientation representing a worst case scenario concerning wind direction. During the 3 yr of field trials the highest levels of gene flow occurred at the site and year with the longes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 38 publications
9
28
0
1
Order By: Relevance
“…This finding is in line with previous studies in which crosspollination frequencies were usually found higher for the outer parts of the recipient field, and declined towards the inner parts due to a higher density of and competition by own pollen of the recipient crop (Devos et al, 2005). Langhof et al (2010), however, evaluated Bt adventitious presence at different depths into the recipient field, and found that cross-fertilization did not follow a regular pattern deep into the field. Therefore, discard of the rows facing Bt source may help to maintain cross-fertilization below a threshold level, but would not completely prevent it.…”
Section: P Galeano Et Alsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is in line with previous studies in which crosspollination frequencies were usually found higher for the outer parts of the recipient field, and declined towards the inner parts due to a higher density of and competition by own pollen of the recipient crop (Devos et al, 2005). Langhof et al (2010), however, evaluated Bt adventitious presence at different depths into the recipient field, and found that cross-fertilization did not follow a regular pattern deep into the field. Therefore, discard of the rows facing Bt source may help to maintain cross-fertilization below a threshold level, but would not completely prevent it.…”
Section: P Galeano Et Alsupporting
confidence: 92%
“…Field situations may differ in a range of conditions, such as acreage, topography, number and direction of pollen sources. Flowering time may also differ, and differences in wind speed and the occurrence of storms during flowering will vary from one case to another (Langhof et al, 2010). As a consequence, results from commercial fields may not be easily comparable, and this information may not be useful to analyze a single factor, for instance, the effect of the distance between GM and non-GM crops on crosspollination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these circumstances, separate edge harvest has just a small effect on the GM content of the total field's harvest and is not as effective as for example in nearly exclusively wind pollinated crop species such as maize, where a considerable amount of outcrossing is found in the first few meters of the donor-facing field edge (e.g. Langhof et al, 2010). Although their study showed that a 5 m wide buffer zone surrounding the non-GM oilseed rape field can reduce outcrossing by about a third, Damgaard and Kjellsson (2005) concluded that isolation distances more effectively reduce pollen-mediated gene flow in oilseed rape than the use of a buffer zone, especially for small recipient fields.…”
Section: Isolation Distance and Separate Edge Harvest As Coexistence mentioning
confidence: 99%